Liver Disease: A Retrospective Hospital Based Study in Addis Ababa-Ethiopia - Erkabu Samson; Demeke Bisrat; Desallegn Hailu; Getachew Selam (Journal of Spleen And Liver Research, 2021)
Background Liver disease has caused significant morbidity and mortality worldwide. Its epidemiologic and clinical pattern, however, is not well characterized in sub-Saharan countries. Objective This study aimed to describe demographic, clinical characteristics, and patterns of liver disease in a community hospital in Addis Ababa, Ethiopia. Method A retrospective hospital-based study was conducted on patients with liver disease admitted at Ras Desta Damtew memorial hospital, in Addis Ababa-Ethiopia, from February 2015 to April 2020. Result Of the total 212 patients majority, 78.8% were male, 49.1% of patients were in the age range of 31-50 with a median age of 42. The most common initial clinical presentation was ascites (87.7 %), and more than half of patients (56.6%) had a history of alcohol misuse documented on their medical charts. Chronic liver disease (cirrhosis) was found in 177 (83.5%), and Hepatocellular Cancer accounted for 7.5% of the patients. Alcohol misuse caused 45% of chronic Liver Disease, followed by Hepatitis B virus infection. Conclusion Chronic liver disease is the most common form of liver disease, and the most affected were middle-aged men. The common cause of chronic liver disease was alcohol followed by hepatitis B virus infection.
Keywords: Liver disease